Practice structure and quality improvement activities among emergency departments in the Emergency Quality (E‐QUAL) Network. Issue 5 (12th May 2020) - Berdahl, Carl T.; Schuur, Jeremiah D.; Rothenberg, Craig; Samadian, Kian; Sharma, Dhruv; Tarrant, Nalani; Goyal, Pawan; Venkatesh, Arjun K.
Abstract: Objectives: Little academic investigation has been done to describe emergency department (ED) practice structure and quality improvement activities. Our objective was to describe staffing, payment mechanisms, and quality improvement activities among EDs in a nationwide quality improvement network and also stratify results to descriptively compare (1) single‐ versus multi‐site EDs and (2) small‐group versus large‐group EDs. Methods: Observational study examining EDs that completed activities for the 2018 wave of the Emergency Quality Network (E‐QUAL), a voluntary network of EDs nationwide that self‐report quality improvement activities. EDs were defined as single‐site or multi‐site based on self‐reported billing practices; additionally, EDs were defined as large‐group if they and a majority of other sites with the same group name also identified as multi‐site. All other sites were deemed small‐group. Results: Data from 377 EDs were included. For staffing, the median number of clinicians was 17 overall (16 single‐site; 19 multi‐site). For payment, 376 of 377 EDs (99.7%) participated in the Merit‐Based Incentive Payment System. Thirty‐five EDs (9.2%) participated in a federal alternative payment model, and 19 (5.0%) participated in a commercial alternative payment model. For quality improvement, single‐ and multi‐site EDs reported similar progress on quality improvement strategies; however, small‐group EDs reported more advanced quality improvement strategies compared to large‐group EDs for 8/10 quality improvement strategies included in a survey (eg, "achieved a formal plan to eliminate waste"). Conclusion: Among EDs in E‐QUAL, staffing, payment, and quality improvement activities are similar between single‐ and multi‐site EDs. Group‐level analysis suggests that practice structure may influence adoption of quality improvement strategies. Future work is needed to further evaluate practice structure and its influence on quality improvement activities and quality.